Dissecting Broadcast Media Advocacy Campaign against Child Trafficking Menace: The Trends and its Implications for Edo State, Nigeria - Sule, Kasimu; Chukwu, Obinna Johnkennedy (Randwick International of Social Science Journal, 2025)
This study examines media advocacy campaigns against child trafficking in Nigeria. The researcher undertook this study with the intention of achieving three objectives; based on these objectives, three research questions were formulated to guide the study. The study was anchored on the social responsibility theory and supported by the agenda-setting theory. The survey method was deemed appropriate for this study. Findings from this study indicate that the broadcast media create awareness about child trafficking in Nigeria; additionally, the media educate people on the dangers of child trafficking and guide public discourse on the topic. Findings also reveal that the broadcast media are highly effective in the campaign against child trafficking in Nigeria. This study recommends that the broadcast media should increase awareness by making stories on child trafficking more prominent. There should be commentary, phone-in programs, interviews, discussions, and other formats on radio and television focused on child trafficking and potential solutions. The broadcast media should also strengthen the fight against trafficking by including a segment in their programs where trafficked victims can share their experiences.